Niz Prešernovih jezikov - Turk, Boštjan Marko (Vestnik za tuje jezike, 2015)
The article deals with the part of Prešeren's poetic work written in German, the obvious lingua franca of the Austro-Hungarian empire. The poet, in spite of good intentions to do so, never published these poems as a whole. He chose a motto from Ovid's Ex Ponto instead: "getico scripsi sermone libellum", which reads: "I wrote a book in a barbaric language". The article tries to find out the reason for identifying German as barbaric. The answer may lie in a particular romantic attitude towards reality, explained by Immanuel Kant. He established the "Copernican turn" in the behaviour of the human knowledge and consciousness. It is the innate structures of the mind that determine the nature of experience. According to him, only through an account of the a-priori principles of the mind can knowledge be validated and objective, and thus lead to reality. This is the path to the modern subjectivity. Prešeren as a romantic poet profoundly integrated Kant's vision in his poetry protesting thus against the predominant German culture of the time.
Keywords: Prešeren, France, 1800-1849; Ovidius Naso, Publius, 43 pr.n.št.-18 n.št.; slovenska poezija; Romanticism; romantika; latinska poezija; nemščina; German; barbarski jezik; Kantov kopernikanski obrat